2011
DOI: 10.1103/physrevlett.106.257601
|View full text |Cite
|
Sign up to set email alerts
|

Theory of High-Temperature Multiferroicity in Cupric Oxide

Abstract: The incommensurate-commensurate phases reported in cupric oxide below 230 K are shown theoretically to realize an inverted sequence of symmetry-breaking mechanisms with respect to the usual sequence occurring in low-temperature multiferroic compounds. The sequence inversion results from a strong triggering-coupling mechanism between two antiferromagnetic order parameters inducing a first-order transition to the multiferroic phase. Such mechanism is favored by the large antiferromagnetic superexchange interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
65
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 16 publications
1
65
1
Order By: Relevance
“…In contrast with the conclusions of Refs. [8][9][10], our analysis based on rigorous symmetry arguments indicates that there must be a collinear intermediate phase (AF3) between the paramagnetic and spiral AF2 states. Such a phase has been shown, both theoretically and experimentally, to occur in other geometrically frustrated antiferromagnets where symmetry allows for uniaxial anisotropy at second order [14,15] For the purpose of this study, a CuO sample was grown using a floating zone technique as described in Ref.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast with the conclusions of Refs. [8][9][10], our analysis based on rigorous symmetry arguments indicates that there must be a collinear intermediate phase (AF3) between the paramagnetic and spiral AF2 states. Such a phase has been shown, both theoretically and experimentally, to occur in other geometrically frustrated antiferromagnets where symmetry allows for uniaxial anisotropy at second order [14,15] For the purpose of this study, a CuO sample was grown using a floating zone technique as described in Ref.…”
mentioning
confidence: 89%
“…However, the authors of the neutron diffraction measurements [6] questioned the possibility of having a direct condensation from a paramagnetic (PM) phase to a spiral magnetic phase. Despite this remark, a recent Landau theory [8], as well as several Monte-Carlo simulations [9,10], appear to support this sequence of magnetic orderings.…”
mentioning
confidence: 92%
“…A phenomenological theory of phase transitions in CuO was suggested in [26], in which the phase transition PM-AF2 was described using the triggering mechanism. This implies the first order character of the PM-AF2 transition.…”
Section: Cuomentioning
confidence: 99%
“…Therefore, one can describe the phase transitions in CuO using the commensurate wave vector k c and account for longwavelength modulation by Lifshitz invariants allowed by the symmetry [20]. Using the monoclinic structure as reference it was shown that the magnetic structure of the phase AF2 is described by two IR's B 1 and B 2 , whereas the phase AF1 by B 2 [20,21,26].…”
Section: Cuomentioning
confidence: 99%
“…1c. This phase exhibits a static electric polarization P b B100 mC m À 2 along b 20,26,27 , the origin of which has been discussed in the context of weakly frustrated intersublattice spin interactions 23 , magnetic degeneracy and the spin-orbit interaction 28 and cross-coupled AFM order parameters 29 . While CuO exhibits ferroelectric hysteresis loops 20 and chiral magnetic domains that can be switched electrically 27 , no substantial uniform static magnetoelectric coupling has been found in polycrystalline CuO up to 7 T 26 , and the AF2 phase appears to be stable to at least 16 T 30 .…”
mentioning
confidence: 99%